2003
DOI: 10.1093/cercor/13.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Difficulty Evoke Anatomically and Pharmacologically Dissociable Brain Activation Dynamics

Abstract: Brain activation is adaptive to task difficulty and practice. We used functional MRI to map brain systems activated by an object-location learning task in 24 healthy elderly volunteers each scanned following placebo and two of four active drugs studied. We distinguished a fronto-striatal system adaptive to difficulty from a posterior system adaptive to practice. Fronto-striatal response to increased cognitive load was significantly attenuated by scopolamine, sulpiride and methylphenidate; practice effects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…Nonetheless, several observations corroborate the notion that the observed SN activity is indeed linked to enhanced dopaminergic neurotransmission: attentional deficits (especially concerning top-down, endogenous attention) have been reported for PD patients, along with deficits in other executive functions (Brown and Marsden, 1988;Yamaguchi and Kobayashi, 1998;Nieoullon, 2002;Cools, 2006). In accord with these findings, pharmacological and lesion studies in animals reported influences of the dopaminergic system on functions related to the recruitment of attentional resources (for review, see Robbins, 2005), and pharmacological investigations in humans have also yielded corroborating results (Clark et al, 1987;Servan-Schreiber et al, 1998;Bullmore et al, 2003). Moreover, demonstrations of a strong correlation between reward-related mesolimbic fMRI responses and rewardrelated striatal dopamine release in the same human subjects ([ 11 C]raclopride displacement PET) suggests a strong relationship between the two measures (Schott et al, 2008).…”
Section: Discussionmentioning
confidence: 70%
“…Nonetheless, several observations corroborate the notion that the observed SN activity is indeed linked to enhanced dopaminergic neurotransmission: attentional deficits (especially concerning top-down, endogenous attention) have been reported for PD patients, along with deficits in other executive functions (Brown and Marsden, 1988;Yamaguchi and Kobayashi, 1998;Nieoullon, 2002;Cools, 2006). In accord with these findings, pharmacological and lesion studies in animals reported influences of the dopaminergic system on functions related to the recruitment of attentional resources (for review, see Robbins, 2005), and pharmacological investigations in humans have also yielded corroborating results (Clark et al, 1987;Servan-Schreiber et al, 1998;Bullmore et al, 2003). Moreover, demonstrations of a strong correlation between reward-related mesolimbic fMRI responses and rewardrelated striatal dopamine release in the same human subjects ([ 11 C]raclopride displacement PET) suggests a strong relationship between the two measures (Schott et al, 2008).…”
Section: Discussionmentioning
confidence: 70%
“…Other pharmacological fMRI studies using oral MPH generally show enhanced cortical and subcortical blood oxygen level-dependent (BOLD) responses in healthy controls or individuals with ADHD (reviewed in ref. 42), which are most consistently shown in the PFC (including the ACC and OFC) and dorsal striatum (43). Nevertheless, disparity in direction of results may also be attributed to other factors [e.g., type of task (it would be important to use a sensorimotor task as an active control task) and severity of impairment (baseline capacity needs to be tested in studies with larger sample sizes)] and remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging and basic research implicate the striatum in the learning and execution of motor programs (35). Recent research in adults indicates striatal engagement with increasing neurocognitive load (36), and animal research suggests that striatal dopaminergic neurons produce error signals (37). (this paragraph doesn't flowperhaps rewrite the preceding 3 sentences to soften the jump from deficient motor regulation to striatal function) Data presented here and elsewhere (34) suggest that motor inhibition deficits in pediatric BPD may reflect a failure to engage the striatum appropriately during failed inhibition.…”
Section: Discussionmentioning
confidence: 99%